Diagnosis and Treatment of Invasive Mucormycosis - Kanda, Yoshinobu (Nihon Ishinkin Gakkai Zasshi, 2023)
Invasive fungal infections are usually observed in severely immunosuppressed patients. The underlying diseases of mucormycosis include diabetes mellitus and hematological malignancies. Rhino-orbital disease is frequent among patients with diabetes, whereas patients with hematological malignancies often develop pulmonary mucormycosis. The prognosis of mucormycosis is extremely poor, and thus early diagnosis and early treatment start are important. However, diagnosis is difficult as its clinical manifestation is similar with that of aspergillosis. There has been no specific serological test for mucormycosis, and biopsy of the involved lesion should be considered. High-dose (5 mg/kg/day) liposomal amphotericin-B is the first line treatment, while azole antifungals with activity against mucormycosis, such as posaconazole or isavuconazole, can be used for refractory or intolerant cases and when switching to oral treatment. Surgical resection or debridement should be considered, if possible, especially for rhino-orbital disease, soft tissue lesion, and single pulmonary lesion, concomitant with antifungal treatment. In addition, reversal of immune function should be tried, as far as possible.